PREECLAMPSIA COMPLICATED WITH PULMONARY EDEMA IN NEWLY DIAGNOSED PERIPARTUM DILATED CARDIOMYOPATHY: CASE REPORT. (June 2022) - Mitevska, Irena; Stanojevic, Verdi; Stojcevski, Saso; Bosevski, Marijan; Jovanova, Silvana; Kostovska, Elizabeta Srbinovska
Abstract : Objective: Pulmonary edema is one of the most serious complications of preeclampsia that should be ruled out in case of dyspnea in a pregnant woman. The prognosis is generally good, however it can indicate underlying unrecognized dilated cardiomyopathy. Design and method: We present a case of 30-year-old woman in 34 weeks of pregnancy was hospitalized at the Gynecology Clinic for preeclampsia. Results: This was the third pregnancy without any previous known cardiovascular disease or known hypertension. Cardiology examination was requested which showed conscious, severely dispnoic and tachycardic patient, with lower leg edema and bilateral pulmonary rales indicating acute pulmonary edema. Blood pressure was 170/100 mmHg, heart rate 130 bpm and saturation 89% with oxygen nasal mask. She reported the presence of headache. Patient was treated for three days with Metil dopa, Nifedipine and corticosteroid therapy of baby lung maturation. She received magnesium sulfate, Verapamil and intravenous Furosemide of 120 mg and the time of pulmonary edema. The patient was not in labor. The ultrasound revealed a monofetal pregnancy and amniotic fluid in normal quantity. Laboratory tests showed mild anemia with normal renal and liver function results. D-dimers were 1320 ng/ml. After stabilization of the patient, a C-section was performed, with the extraction of healthy newborn with an APGAR at 10/10th. There were no post-operative complications. There was marked disappearance of dyspnea within 72 hours, and stabilization of blood pressure. Patient was transferred to the cardiology clinic. Echocardiography showed signs of dilated cardiomyopathy with EF 30% and absent valvopathy. She was put on heart failure treatment with ACE inhibitor, beta blocker, MRA antagonist, furosemide, bromocriptine and LMWH. We received significant clinical improvement during the hospitalization. She was discharged after 6 days in NYHA class II. Conclusions: Acute pulmonary edema is a rare complication, but leading cause of death in women with pre-eclampsia. Diagnosis of peripartum cardiomyopathy requires heightened awareness among multidisciplinary patient care teams and a high degree of suspicion. Many patients with peripartum cardiomyopathy recover within 3 to 6 months of disease onset, but recovery might occur as late as 48 months postpartum